2009
DOI: 10.1063/1.3264944
|View full text |Cite
|
Sign up to set email alerts
|

Free energy landscape for the translocation of polymer through an interacting pore

Abstract: Free energy landscapes for polymer chain translocating through an interacting pore are calculated by using exact enumeration method. A potential barrier exists at weak attractive or repulsive polymer-pore interaction and it changes to a potential well with the increase in the attraction. The result reveals that there is a free translocation point where polymer is free of energy barrier. Using the free energy landscape, the translocation time tau for polymer worming through the pore and the migration time tau(m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…We find that the translocation time τ is strongly dependent on E. For the unbiased case (F = 0) and weak driving cases (F = 0.1 and 0.2), τ first decreases fast with E and then increases slowly with E, and a minimum is found near E = −1. The reason for such a nonmonotonic dependence is that the free-energy landscape or the translocation is dependent on the polymer-pore interaction [46]. It was found that a free-energy barrier for a noninteracting or weak attractive pore will change to a free-energy well for a strong attractive pore.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We find that the translocation time τ is strongly dependent on E. For the unbiased case (F = 0) and weak driving cases (F = 0.1 and 0.2), τ first decreases fast with E and then increases slowly with E, and a minimum is found near E = −1. The reason for such a nonmonotonic dependence is that the free-energy landscape or the translocation is dependent on the polymer-pore interaction [46]. It was found that a free-energy barrier for a noninteracting or weak attractive pore will change to a free-energy well for a strong attractive pore.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…The interaction can change the free-energy landscape for polymer translocation [45]; for instance, a free-energy barrier for a neutral pore changes to a free-energy well for a strong attractive pore [46]. Thus the translocation time was highly dependent on the interaction [46]. Up until now, the dependence of the scaling behavior of translocation time on the interaction has not been clear.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The polymer is thus trapped in the free-energy well, and it will cost a long time for the polymer to leave the channel. 19,37 Again, the time for the polymer translocation through the strong attractive pore is long. As a result, there is a minimum time at a proper attraction between the polymer and the pore.…”
Section: Introductionmentioning
confidence: 99%
“…And there is a free translocation point where the polymer is free of both free-energy barrier and freeenergy well. 37 For the repulsive and weak attractive pores, it is difficult for the polymer to enter the pore but is easy for the polymer to leave the pore, therefore the time for the polymer translocating from the cis side to the trans side is long. Whereas for the strong attractive pore, it is easy for the polymer to enter the channel but is difficult for it to leave.…”
Section: Introductionmentioning
confidence: 99%